2012
DOI: 10.1007/s11250-012-0124-2
|View full text |Cite
|
Sign up to set email alerts
|

Models of highly pathogenic avian influenza epidemics in commercial poultry flocks in Nigeria and Ghana

Abstract: State-scale and premises-scale gravity models for the spread of highly pathogenic avian influenza (H5N1) in Nigeria and Ghana were used to provide a basis for risk maps for future epidemics and to compare and rank plausible culling and vaccination strategies for control. Maximum likelihood methods were used to fit the models to the 2006–2007 outbreaks. The sensitivity and specificity of the state-scale model-generated probabilities that any given state would be involved in an epidemic were each 57 %. The premi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 20 publications
(24 reference statements)
1
23
0
Order By: Relevance
“…A hot-spot analysis indicated that LGAs with a similar number of positive model simulations were clustered together and that the locations of 2006–2007 epidemics were generally within statistically “hot” zones while “cold” zones contained fewer or no epidemic events. While our model results match the smoothed incidence risk of H5N1 during the outbreak from 2005–2008 compiled by Henning et al [ 14 ], as well as the risk of Nigerian states calculated by Pelletier et al [ 50 ], we show slightly less risk associated with northern Nigeria. This may be due the fact that the outbreaks were first concentrated in the northern zones of Nigeria during the first phase of the epidemic [ 21 ] and thus, was likely an initial introduction site.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…A hot-spot analysis indicated that LGAs with a similar number of positive model simulations were clustered together and that the locations of 2006–2007 epidemics were generally within statistically “hot” zones while “cold” zones contained fewer or no epidemic events. While our model results match the smoothed incidence risk of H5N1 during the outbreak from 2005–2008 compiled by Henning et al [ 14 ], as well as the risk of Nigerian states calculated by Pelletier et al [ 50 ], we show slightly less risk associated with northern Nigeria. This may be due the fact that the outbreaks were first concentrated in the northern zones of Nigeria during the first phase of the epidemic [ 21 ] and thus, was likely an initial introduction site.…”
Section: Discussionsupporting
confidence: 84%
“…This may be due the fact that the outbreaks were first concentrated in the northern zones of Nigeria during the first phase of the epidemic [ 21 ] and thus, was likely an initial introduction site. Pelletier et al [ 50 ] demonstrated that location of the introduction of H5N1 into Nigeria greatly impacts the spread of a disease outbreak. As Pelletier et al [ 50 ] point out with H5N1 in Nigeria; transmission is a stochastic process and not all introductions lead to major epidemics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The actions taken during outbreaks included notification of outbreaks to OIE, demarcation of culling and surveillance areas, culling of birds in the outbreak areas, an absolute ban on movement of poultry and products from the culling and surveillance zones, disposal of dead birds, instant compensation for culling, clean-up and disinfection, and post-operation surveillance [ 63 , 84 ]. After the outbreaks in 2006, active surveillance systems were implemented in wild birds, domestic poultry, and the human population throughout both countries [ 63 , 82 , [85] , [86] , [87] , [88] ].…”
Section: Discussion: the Dynamics Of Intersectoral Collaborationsmentioning
confidence: 99%
“…While the case-control literature is sometimes used to justify the assumptions that qualitatively underpin architecture of mathematical models of infectious disease transmission (e.g. Pelletier et al., 2012; Rorres et al, 2011), I have been unable to find any examples in which the actual value of the odds ratios measured during case-control studies have been used directly to estimate model parameters.…”
Section: Discussionmentioning
confidence: 99%